2006
DOI: 10.1177/154405910608501010
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of School Dental Screening: a Cluster-randomized Control Trial

Abstract: Dental screening of children in schools is undertaken in many countries. There is no evidence that this activity is effective. The objective of our study was to determine if school dental screening of children reduces untreated disease or improves attendance at the population level. A four-arm cluster-randomized controlled trial was undertaken in the northwest of England. In total, 16,864 children aged 6-9 years in 168 schools were randomly allocated to 3 test groups, which received screening according to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 5 publications
1
73
0
Order By: Relevance
“…12,13 This study provides some indications as to why this should be the case. Positive consent is now advised for screening examinations 11 and this will further reduce its effectiveness due to anticipated low levels of response, particularly in more disadvantaged areas.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…12,13 This study provides some indications as to why this should be the case. Positive consent is now advised for screening examinations 11 and this will further reduce its effectiveness due to anticipated low levels of response, particularly in more disadvantaged areas.…”
Section: Discussionmentioning
confidence: 89%
“…A recently conducted large randomised controlled trial of school dental screening has demonstrated that the programme is not effective at reducing dental disease or improving attendance at the population level. 13 A supplementary study that followed up screened positive children reported that less than half of them attended the dentist and of those that did attend, approximately half failed to complete their dental treatment. 14 The qualitative study reported here found that whilst parents recognised they had prime responsibility to ensure that their children attended a dentist, many provided reasons why this was diffi cult to realise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Screening can only be regarded as being successful if it offers health improvement either for the population as a whole, or the screened positive individual, or both. 2 Although no benefit was observed at the population level, it is possible that school dental screening has a role in reducing dental health inequalities by encouraging individual children with dental needs to attend and receive appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%
“…• Dental screening, in the present conditions prevailing in England, was ineffective to achieve the objectives of increasing attendance and active management of disease 7,8 • That both the providers (salaried dentists) 9 and the end users (parents, teachers, and school nurses) identi fied a failing in the process was the follow-up procedure or rather the lack of it 10 • The fluoridation of water would improve dental health for children; 11 reinforcing other researchers. 12 The use of fluoridated milk might be successful, but required further research 13 • The type of dental health education provided in general dental practice was usually about sugar consumption and brushing, varied between practitioners, there was a lack of clarity about the use of fl uorides, 14 lack of visual aids and leafl ets, and was targeted more upon the basis of the dentist's assessment of parental motivation.…”
Section: Introductionmentioning
confidence: 99%